The art of articulation: The electroacoustic music of Horacio Vaggione. - Roads, Curtis (Contemporary Music Review, 2005)
The composition of music has evolved into an interactive process of directly sculpting sound morphologies on multiple time scales. A prime example is the electroacoustic music of Horacio Vaggione. This music's complexity and subtlety challenges mere textual description, posing formidable problems of discourse. This article traces the aesthetic and technical path followed by the composer during his career, and in so doing begins the task of developing a new analytical vocabulary. Fortunately, Professor Vaggione has written a considerable amount about his aesthetic approach. For this article, I have relied on Vaggione's texts as well as his extensive comments on a draft of this article.